2006
DOI: 10.1007/s00442-005-0347-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism, activity budget and synchrony in groups of sheep

Abstract: The activity budget hypothesis has been proposed to explain the social segregation commonly observed in ungulate populations. This hypothesis suggests that differences in body size--i.e. between dimorphic males and females--may account for differences in activity budget. In particular, if females spend more time grazing and less time resting than males, activity synchrony would be reduced. Increased costs of maintaining synchrony despite differences in activity budget would facilitate group fragmentation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
1
28
1
1
Order By: Relevance
“…So, the males and females would separate to aggregate in same-sex groups, respectively, to keep behavioral synchrony (Ruckstuhl 1998(Ruckstuhl , 2006. Some studies support the activity budget hypothesis (Conradt 1998;Ruckstuhl and Kokko 2002) and some do not (Michelena et al 2006;Mooring et al 2003;Yearsley and Perez-Barberia 2005). For example, studies on red deer (Cervus elaphus) showed that mixed-sex groups were more likely to break up than single-sex groups because of sex differences in activity rhythm (Conradt 1998), and this result supports the activity budget hypothesis.…”
supporting
confidence: 59%
“…So, the males and females would separate to aggregate in same-sex groups, respectively, to keep behavioral synchrony (Ruckstuhl 1998(Ruckstuhl , 2006. Some studies support the activity budget hypothesis (Conradt 1998;Ruckstuhl and Kokko 2002) and some do not (Michelena et al 2006;Mooring et al 2003;Yearsley and Perez-Barberia 2005). For example, studies on red deer (Cervus elaphus) showed that mixed-sex groups were more likely to break up than single-sex groups because of sex differences in activity rhythm (Conradt 1998), and this result supports the activity budget hypothesis.…”
supporting
confidence: 59%
“…Other authors have noted considerable differences in individual vigilance levels between females and males (Childress and Lung 2003;Michelena et al 2006;Monclus and Rodel 2008). Some have argued that females are often more vigilant than males because males are larger and stronger, and therefore can escape from predators more easily (Clutton-Brock et al 1982).…”
Section: Discussionmentioning
confidence: 97%
“…Studies on vigilance have shown sex to be an important factor influencing vigilant behavior (Hunter and Skinner 1998;Cameron and Du Toit 2005;Michelena et al 2006;Li and Jiang 2008). Although several studies have shown that the vigilance levels are usually different between females and males, reports have not suggested any consistent pattern regarding the more vigilant sex (Elgar 1989;Laundre et al 2001;Cameron and Du Toit 2005).…”
Section: Introductionmentioning
confidence: 94%
“…In sexually dimorphic ungulates, it is predicted that the mass-speciWc energy requirements of sub-adult males are higher than those of fully grown adults, due to their smaller body sizes and the substantial energetic costs of growth (Ruckstuhl et al 2003). Ultimately, this could lead to segregation between age groups as well as sex (Ruckstuhl 1998;Bon et al 2001;Michelena et al 2006).…”
Section: Discussionmentioning
confidence: 97%